On a q-fractional variant of nonlinear Langevin equation of different orders - B. Ahmad; J. J. Nieto; Alsaedi, A.; Al-Hutami, H. (Հայաստանի ԳԱԱ)
In this paper we introduce a q-fractional variant of nonlinear Langevin equation of different orders with q-fractional antiperiodic boundary conditions.
Keywords: Mathematics; Science; General Works